The 39 clues : Beyond the grave - Watson, Jude. (New York : Scholastic Ltd., 2012)
Amy and Dan are hot on the trail of the fourth Clue, but their ruthless relatives will stop at nothing to eliminate them from the competition. Their hunt leads them to an ancient city that has been a hotbed of Cahill activity for centuries. The clock is ticking for Amy and Dan.
Keywords: GAMES -- FICTION